Acid/Base‐Mediated Uptake and Release of Halide Anions with a Preorganized Aryl‐Triazole Foldamer. Issue 21 (1st April 2015) - Zhao, Wei; Wang, Ying; Shang, Jie; Che, Yanke; Jiang, Hua
Abstract A new approach for the construction of artificial receptors capable of selectively uptake and release of halides to mimic the biological halide ions pumps is developed, in which the preorganized aryl‐triazole foldamer was designed to bear a resorcinolic group in the central strand as a switch regulator. By using 1, 8‐diazabicyclo[5.4.0]undec‐7‐ene/picric acid as the trigger, the foldamer can be switched between "w"‐shape and helical conformation. Due to the large, half‐open cavity as well as the additional electrostatic repulsion between oxyanions and guest halide, the foldamer in "w"‐shape possesses a much weaker affinity for chloride, bromide, and iodide anions than those in the helical conformation in 6:94 (v/v) [D6]DMSO/CDCl3. When the foldamer and chloride ions have the same initial concentrations of 1 mM, 70 % chloride ions in the solution could be reversibly bound or released upon switching.